Diffusion-weighted MR imaging in postoperative follow-up: Reliability for detection of recurrent cholesteatoma - ÇİMŞİT, NURİ ÇAGATAY (ELSEVIER IRELAND LTD, 2010)
Introduction: Cholesteatoma is a progressively growing process that destroy the neighboring bony structures and treatment is surgical removal. Follow-up is important in the postoperative period, since further surgery is necessary if recurrence is present, but not if granulation tissue is detected. This study evaluates if diffusion-weighted MR imaging alone can be a reliable alternative to CT, without use of contrast agent for follow-up of postoperative patients in detecting recurrent cholesteatoma. Materials and methods: 26 consecutive patients with mastoidectomy reporting for routine follow-up CT after mastoidectomy were included in the study, if there was loss of middle ear aeration on CT examination. MR images were evaluated for loss of aeration and signal intensity changes on diffusion-weighted sequences. Surgical results were compared with imaging findings. Results: Interpretation of MR images were parallel with the loss of aeration detected on CT for all 26 patients. Of the 26 patients examined, 14 were not evaluated as recurrent cholesteatoma and verified with surgery (NPV: 100%). Twelve patients were diagnosed as recurrent cholesteatoma and 11 were surgically diagnosed as recurrent cholesteatoma (PPV: 91.7%). Four of these 11 patients had loss of aeration size greater than the high signal intensity area on DWI, which were surgically confirmed as granulation tissue or fibrosis accompanying recurrent cholesteatoma. Conclusion: Diffusion-weighted MR for suspected recurrent cholesteatoma is a valuable tool to cut costs and prevent unnecessary second-look surgeries. It has the potential to become the MR sequence of choice to differentiate recurrent cholesteatoma from other causes of loss of aeration in patients with mastoidectomy. (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: Recurrent cholesteatoma; Diffusion-weighted MR; Postoperative